2022
DOI: 10.1002/tcr.202200005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Modified Cap Analogs: Synthesis, Biochemical Properties, and mRNA Based Vaccines

Abstract: The recent FDA approval of the mRNA vaccine for severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) emphasizes the importance of mRNA as a powerful tool for therapeutic applications. The chemically modified mRNA cap analogs contain a unique cap structure, m 7 G[5′]ppp[5′]N (where N=G, A, C or U), present at the 5′‐end of many eukaryotic cellular and viral RNAs and several non‐coding RNAs. The chemical modifications on cap analog influence orientation's nature, translational effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 80 publications
0
32
0
Order By: Relevance
“…Various cap analogs with different structural features have been developed to prepare capped mRNAs by IVT 18 . First to mention are the dinucleotide cap analogs ARCAs 20,21,37,54,56 , which were designed to control the direction of introduction of the dinucleotide cap analog m 7 G(5')ppp(5')G. It was reported that methylation of the 2' or 3' hydroxyl group completely controlled the direction of strand elongation, resulting in an approximately 2-3-fold increase in mRNA translation activity in cultured cells 54,56 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cap analogs with different structural features have been developed to prepare capped mRNAs by IVT 18 . First to mention are the dinucleotide cap analogs ARCAs 20,21,37,54,56 , which were designed to control the direction of introduction of the dinucleotide cap analog m 7 G(5')ppp(5')G. It was reported that methylation of the 2' or 3' hydroxyl group completely controlled the direction of strand elongation, resulting in an approximately 2-3-fold increase in mRNA translation activity in cultured cells 54,56 .…”
Section: Discussionmentioning
confidence: 99%
“…The key step in synthesizing cap analogs is synthesizing the corresponding diphosphate by phosphorylation of guanosine derivatives. For the synthesis of cap analogs known as the ARCA derivatives, protocols consisting of monophosphorylation by the Yoshikawa method using phosphoryl chloride, activation of monophosphate thorough phosphorimidazolide formation, and diphosphate formation by reaction with alkylammonium phosphate were applied 18 . However, this method is complicated because it is based on the stepwise introduction of phosphate groups and requires multiple purifications with aqueous solvents, such as ion exchange and reversed-phase chromatography.…”
Section: Design and Synthesis Of Dinucleotide Purecap Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It is well known in the literature that the chemically modified capped mRNA plays a major role in terms of binding affinity, orientation's nature, nuclear stability, and translational efficiency. 3−7 The employment of the synthetic m 7 GpppNderived dinucleotide cap analogue lacks the 2′-OMe moiety at the N2 nucleotide, whereas synthetic trinucleotide cap analogues have the built-in 2′-OMe moiety at the N2 nucleotide, and the resulting in vitro transcribed mRNAs using these two analogues will have a Cap 1 structure. 7 Extraordinarily, the trinucleotide cap analogue outclasses the dinucleotide cap analogue in terms of capping efficiency and translational properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3−7 The employment of the synthetic m 7 GpppNderived dinucleotide cap analogue lacks the 2′-OMe moiety at the N2 nucleotide, whereas synthetic trinucleotide cap analogues have the built-in 2′-OMe moiety at the N2 nucleotide, and the resulting in vitro transcribed mRNAs using these two analogues will have a Cap 1 structure. 7 Extraordinarily, the trinucleotide cap analogue outclasses the dinucleotide cap analogue in terms of capping efficiency and translational properties. 10,11 Additionally, the presence of the 2′-OMe group in cap 1 has the strong ability to distinguish between self RNA in the innate immune system and nonself RNA that assists to effectively suppress pathogenesis and viral replication.…”
Section: ■ Introductionmentioning
confidence: 99%